Fiscal Decentralization in Indonesia: Does It Curb the Quality of Environment? - Hawari, Adam; Alyasa, Faisal Madjid; Akbar, Muhammad Reyhan; Sihaloho, Estro Dariatno (Journal of Economics Research and Social Sciences, 2024)
Local authorities have played an enormous role in maintaining the sustainability of the environment through decentralization. While decentralization could improve the quality of the environment as an attribute of public good provision, it could also harm the environment by setting low environmental standards to boost environment-related business. In addition, the Environmental Quality Index (IKLH) from various provinces has shown fluctuations in the past ten years. With this ambiguous effect of decentralization, this study aims to disentangle the effect of decentralization on the quality of the environment in Indonesia. This study utilizes Indonesia’s provincial-level data in 33 provinces from 2010 to 2020. In order to solve the model's suffering endogeneity problem, the two-stage least square panel-instrumental variable method is performed. The main results demonstrate that fiscal decentralization and its square significantly affect environmental quality. Its square indicates a nonlinear U-shaped relationship, that in the low-level stage of decentralization tends to harm the environment until the turning point. In addition, this research also suggests the positive but weak effect of Intergovernmental Fiscal Transfer (IFT) on environmental quality. Considering all the results, this research infers that decentralization curbs the quality of the environment in Indonesia and, to some extent, contributes to maintain environmental quality. Therefore, local authorities have a significant role in promoting green regulation to enhance environmental quality and this also reaffirms the importance of green indicators in local budgeting.